Alice’s Anxieties and Defense Mechanisms in Tim Burton’s Alice in Wonderland - C.A.O Wahjudi; D. Setiawan (Kata Kita: Journal of Language, Literature, and Teaching, 2013)
There are negative assumptions on fantasy that it is unrealistic and considered as immature and unacceptable. However, there are times when fantasy is the only way to cope the problems in the real life. In this study, I am going to analyze Alice in Wonderland (2010) movie in order to find out why Alice creates a fantasy of Wonderland. Using the theory of Freudian Psychology, I find that the causes of Alice creating Wonderland are three anxieties which are anxiety on tradition, love, and loss. These anxieties lead Alice to use two defense mechanisms, which are blocking her desire and creating Wonderland. Here, Alice’s Wonderland serves to solve her problem in the real life and satisfy her desires or ‘id’. In conclusion, fantasy is not always negative, but it can be positive.Alice’s Anxieties and Defense Mechanismsin Tim Burton’s Alice in Wonderland